2003
DOI: 10.1111/1469-8986.00072
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability in acute psychosis

Abstract: Heart rate variability (HRV) provides reliable tools to assess the integrity and reactivity of autonomic nervous function. Our aim was to examine HRV in the resting condition and during different mental loads in acute psychosis compared to healthy controls. HRV was measured in 17 first-episode drug-naive patients with psychosis and 21 healthy controls during oddball tasks and while performing the Wisconsin Card Sorting Test. A discrete event series was constructed by an adaptive QRS detector algorithm and powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
60
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 41 publications
7
60
1
2
Order By: Relevance
“…However, there is ample evidence that a dysfunction of the autonomic nervous system (ANS), determined by investigating heart rate variability (HRV), is obviously present in schizophrenia patients. These studies found a vagal withdrawal and a sympathetic predominance for these patients, as well as in part for their healthy first-degree relatives [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 75%
“…However, there is ample evidence that a dysfunction of the autonomic nervous system (ANS), determined by investigating heart rate variability (HRV), is obviously present in schizophrenia patients. These studies found a vagal withdrawal and a sympathetic predominance for these patients, as well as in part for their healthy first-degree relatives [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 75%
“…224,225 A more important question for future research may be what impact age and earlier manifestions of the disorder have on changes in HRV over time, including first-episode and prodromal periods, as symptoms change or worsen. 65,226,227 Additionally, the inclusion of cross-sectional studies in the case-control analysis does not address the question of whether reduced vagal control in these populations is part of a potential mechanism placing these individuals at a greater risk for cardiovascular disease, or whether reduced HRV in these groups compared to controls is actually a downstream effect of altered neural pathways that control autonomic regulation of the heart. 228 Our search strategy included other classes of psychotropic medications (e.g., mood stabilizers, benzodiazepines) and …”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] In particular, a disease-associated decrease in vagal modulation causes reduced heart rate variability (HRV) and diminished baro-reflex sensitivity (BRS). 2 HRV describes the continuous interplay between sympathetic and parasympathetic modulation of heart rate that reflects information on autonomic flexibility and responsiveness.…”
Section: Introductionmentioning
confidence: 99%